Occupational radiation exposure of neurointerventionalists during endovascular stroke treatment - Weyland, Charlotte S.; Jesser, Jessica; Bourgart, Isabella; Hilgenfeld, Tim; Breckwoldt, Michael O.; Vollherbst, Dominik; Schmitt, Niclas; Seker, Fatih; Bendszus, Martin; Möhlenbruch, Markus Alfred (European journal of radiology, 2023)
Background - Radiological neuro-interventions, especially endovascular stroke treatment (EST), are increasing in case numbers worldwide with increasing occupational radiation exposure. Aim of this study was to define the radiation exposure of neurointerventionalists (NI) during EST and to compare the accumulated dose reaching the left arm with the left temple. - Methods - This is a prospective observational study in a tertiary stroke center conducted between 11/2021 and 07/2022. Radiation exposure was measured using real time dosimetry with dosimeters being carried by the NI during EST simultaneously at the left temple and left arm. The effective dose [µSV] per dose area product (DAP) and potential influencing factors were compared in univariate analysis between the two dosimeter positions. - Results - In total, 82 ESTs were analyzed with a median DAP of 6179 µGy*m2 (IQR 3271 µGy*m2-11720 µGy*m2). The accumulated dose at the left arm and left temple correlated with the DAP and fluoroscopy time of the EST (DAP and arm: p = 0.01, DAP and temple: p = 0.006). The radiation exposure (RE) showed a wide range and did not differ between the two dosimeter positions (median, IQR arm 7 µSV, IQR 3.1-16.9 µSV, min. 0.3 µSV max. 64.5 µSV) vs. head 7 µSv, IQR 3.2-17.4 µSV, min. 0.38 µSV, max. 48.6 µSV, p = 0.94). Occupational RE depends on the number of thrombectomy attempts, but not the target vessel occlusion location or the NI’s body height. - Conclusion - Neurointerventionalists experience a generally low but very variable radiation exposure during EST, which depends on the intervention’s fluoroscopy time and dose area product as well as thrombectomy attempts but does not differ between left temple and left arm.
Gesehen am 08.08.2023